Effect on mechanical properties of hybrid blended coconut coir/paraffin wax/LDPEE - Rassiah, Kannan; Chik, Mohd As'ri; Yaakob, Mohd Yuhazri; Haeryip Sihombing (UTHM Publisher, 2011)
The use of natural fibers as the fillers for plastic has been rapidly expanding, especially wood fibers. This is due to materials of wood offers many advantages as inorganic fillers (such as low price, biodegradability, renewability, recycle-ability, low density and others). In addition, this is also due to the dramatic increasing of interest of using biomass materials as the replacements for glass fiber into reinforced thermoplastic composites. In this study, wood plastic composites used are the filled thermoplastics which primarily consisted of wood fiber and thermoplastic polymer. While, the purpose of this research is to find out the optimum conditions of the wax and coconut coir produced by inducing LDPE. The experiment carried out is by mixing the wax, coconut coir and LDPE into eight new polymer compositions, in which the higher value of the tensile strength and hardness are obtained by mixing between 6 wt. % coconut coir with 4 wt. % wax, rather than to pure LDPE, that is 9.236 MPa and 3HV. Although the strength impact is decreased with value as much as 60.95 % compared to original conditions, the SEM analysis proved that the composition of 90 wt. % LDPE, 4 wt. % wax and 6 wt. % coconut coir is the best weight ratios for mechanical characteristics and bonding between reinforced material and matrix material. Here, the LDPE, wax and coconut coir mixture produces a new hybrid polymer and alters the properties of pure LDPE.